Correlation between alveolar recruitment/derecruitment and inflection points on the pressure-volume curve - DiRocco, Joseph D; Carney, David E; Nieman, Gary F (Intensive care medicine, 2007)
To determine whether individual alveolar recruitment/derecruitment (R/D) is correlated with the lower and upper inflections points on the inflation and deflation limb of the whole-lung pressure-volume (P-V) curve. Prospective experimental study in an animal research laboratory. Five anesthetized rats subjected to saline-lavage lung injury. Subpleural alveoli were filmed continuously using an in vivo microscope during the generation of a whole-lung P-V curve using the super syringe technique. Alveolar R/D was correlated to the calculated inflection points on both limbs of the P-V curve. There was continual alveolar recruitment along the entire inflation limb in all animals. There was some correlation (R2=0.898) between the pressure below which microscopic derecruitment was observed and the upper inflection point on the deflation limb. No correlation was observed between this pressure and the lower inflection point on the inflation limb. In this physiological experiment in lungs with pure surfactant deactivation we found that individual alveolar recruitment measured by direct visualization was not correlated with the lower inflection point on inflation whereas alveolar derecruitment was correlated with alveolar derecruitment on deflation. These data suggest that inflection points on the P-V curve do not always represent a change in alveolar number.